2017
DOI: 10.4236/ce.2017.812132
|View full text |Cite
|
Sign up to set email alerts
|

Secondary School Students’ Mastery of Integrated Science Process Skills in Siaya County, Kenya

Abstract: The study investigated secondary school students' mastery of Integrated Science Process Skills (ISPS) among co-educational schools and the influence of grade level, gender, and school location in Siaya County, Kenya. The study used a causal-comparative design with purposive sampling technique. A 30-item Test of Integrated Science Process Skill (TISPS) developed by Kazeni (2005) was administered. The instrument assesses the skills of controlling variables, defining operationally, formulating hypotheses, experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
1
10
1
2
Order By: Relevance
“…Although most teachers were found not to have difficulties applying the elements of SPS, as shown in Table 6, but it is not the case to some students. This coincides with the findings of a study conducted on secondary school students showed that the mastery of ISPS, namely identifying variables, defining operationally, identifying hypotheses, interpreting data and graphs and designing experiments, are at a moderate level with elements of operationally defining skills are in the lowest level (Ong & Johairi, 2010;Ongowo, 2017;Yew & Sunita, 2015). These findings are also supported by a study conducted by Lue (2020).…”
Section: Is There a Need For Online Module Development To Applysupporting
confidence: 86%
See 1 more Smart Citation
“…Although most teachers were found not to have difficulties applying the elements of SPS, as shown in Table 6, but it is not the case to some students. This coincides with the findings of a study conducted on secondary school students showed that the mastery of ISPS, namely identifying variables, defining operationally, identifying hypotheses, interpreting data and graphs and designing experiments, are at a moderate level with elements of operationally defining skills are in the lowest level (Ong & Johairi, 2010;Ongowo, 2017;Yew & Sunita, 2015). These findings are also supported by a study conducted by Lue (2020).…”
Section: Is There a Need For Online Module Development To Applysupporting
confidence: 86%
“…One of the goals in science education is to acquire Science Process Skills (SPS), a skill required by a person to solve problems and issues faced in daily life (Yang & Tsai, 2010). In the construction of scientific knowledge and conceptual change, most science curriculum makers acknowledged science process skills as an important tool (Ongowo, 2017). According to Edy Hafizan et al, (2012), a science curriculum that emphasizes SPS will enable students to improve their mastery of critical thinking skills, creative thinking skills and problem-solving skills, which are the skills needed to fulfill future jobs requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Jack (2018) also found that the integrated science process was difficult for students. However, Ongowo (2017) analyzing the level of mastery of integrated SPSs of lower secondary and upper secondary students found them to have achieved an average level of acquisition with the highest performance for the highest grade. Considering these research findings from other countries, it is important to emphasize that, although the level of understanding of integrated SPSs is average or low in most developing countries, the performance shown by the students in this study is immensely poor and of great concern in learning and understanding of science concepts.…”
Section: Discussionmentioning
confidence: 95%
“…They receive information about items or occurrences in their environment using all their senses. Through hands-on activities such as science experiments, children engage their various senses by touching, feeling, moving, observing, listening, and smelling, as well as occasionally testing objects in a controlled environment (Ongowo, 2017). This assists pupils in progressing from concrete to more complex thinking levels (Wood et al, 2007), hence promoting higher order thinking abilities necessary for 21st century success.…”
Section: Discussionmentioning
confidence: 99%